2018
DOI: 10.5902/1980509835360
|View full text |Cite
|
Sign up to set email alerts
|

Vantagem Comparativa E Matriz De Competitividade Do Mate Brasileiro E Argentino, No Período De 1997-2011

Abstract: Esse artigo teve por objetivo analisar o desempenho das exportações do Brasil e da Argentina no mercadointernacional de mate. O método de análise utilizado refere-se ao Índice de Vantagem Comparativa Revelada(IVCR) do mate brasileiro e argentino, durante o período de 1997 a 2011. Inicialmente, foi verificada aexistência de quebras estruturais das séries temporais e depois, foram averiguados a taxa de crescimentode mercado e o Índice de Vantagem Comparativa Revelada Simétrica (IVCRS) que foram utilizados paraid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
1
0
3
Order By: Relevance
“…Therefore, the authors reported that there is a possible threat to the continuity of the yerba mate producers business, as the sector presents, among other flaws, the lack of strategic planning for commercialization, distribution, and marketing (WOLF; PEREIRA, 2016). Schirigatti et al (2018) analyzed the performance of exports from Brazil and Argentina in the international mate market. For this, they used the Index of the Revealed Comparative Advantage (IVCR) of Brazilian and Argentine mate, taking the period from 1997 to 2011 as a reference.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the authors reported that there is a possible threat to the continuity of the yerba mate producers business, as the sector presents, among other flaws, the lack of strategic planning for commercialization, distribution, and marketing (WOLF; PEREIRA, 2016). Schirigatti et al (2018) analyzed the performance of exports from Brazil and Argentina in the international mate market. For this, they used the Index of the Revealed Comparative Advantage (IVCR) of Brazilian and Argentine mate, taking the period from 1997 to 2011 as a reference.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Para fins metodológicos, este artigo emprega o índice de vantagem comparativa revelada como instrumento de pesquisa, o qual foi estruturado por Balassa (1965). Esse índice é fundamentado na teoria clássica ricardiana e oportuniza analisar a competitividade, por meio de informações passadas originadas pelas transações comerciais (SCHIRIGATTI et al, 2018).…”
Section: Fundamentação Teóricaunclassified
“…Para fins metodológicos, diante das teorias propostas, o presente artigo utilizará como instrumento de pesquisa o Índice de Vantagem Comparativa Revelada, o qual foi formulado por Balassa (1965). O respectivo índice é baseado na teoria clássica ricardiana e possibilita desenvolver uma análise da competitividade com base nas informações passadas dos fluxos comerciais (SCHIRIGATTI et al, 2018).…”
Section: Fundamentação Teóricaunclassified